Delayed Onset of Lactogenesis Is Associated with Suboptimal Breastfeeding Practices in the TMCHC Study: A Prospective Cohort Study (OR30-05-19). (24th October 2019) - Huang, Li; Chen, Xi; Li, Qian; Lin, Lixia; Gao, Duan; Hong, Miao; Yang, Xuefeng; Hao, Liping; Yang, Nianhong
Abstract: Objectives: Whether delayed onset of lactogenesis (delayed OL) was linked to successful breastfeeding is unclear. We aimed to assess the association between delayed OL and breastfeeding practices in Chinese women. Methods: Women form the TMCHC (Tongji Maternal and Child Health Cohort) study, who had OL assessment by face-to-face interview at day 4 postpartum and breastfeeding practices collected at 3, 6 and 12 months postpartum, were selected for the study. Poisson regression and Cox regression were used to identify the association between delayed OL and breastfeeding practices. Results: Delayed OL was reported by 17.7% of the 2691 participants. After adjusting for maternal age, ethnicity, education, income, parity, pre-pregnancy BMI, GDM, gestational weight gain, gestational age, delivery mode, birth weight and breastfeeding information at day 1 postpartum, delayed OL was significantly associated with a higher risk of an inability to sustain full breastfeeding at 3 months postpartum (RR:1.31, 95% CI: 1.16, 1.48) and 6 months postpartum (RR:1.17, 95% CI: 1.07, 1.28), when compared with timely OL. Delayed OL was also significantly associated with early termination of any breastfeeding (HR:1.17, 95% CI: 1.01, 1.34) in adjusted model. Conclusions: This study shows that women with delayed OL had a higher risk of suboptimal breastfeeding practices. Comprehensive efforts should be targeted towards women with delayed OL to promote breastfeeding. Funding Sources: Funding was received from National Program on Basic Research Project of China (NO.2013FY114200) and the Fundamental Research Funds for the Central Universities (HUST2016YXZD040) for Nianhong Yang. Supporting Tables, Images and/or Graphs